Activity Analysis In Teacher Education: a Case Study of Classroom Query, Representation and Data-Driven Choice Making: Exploring the Impact of Action Research on Teacher Learning and Classroom Practices (Journal of Advances and Scholarly Researches in Allied Education, 2013)
One of the growinginterests in teacher education lies in how and what teachers learn across timeand space in the complex ecologies and technologies of today's society. Teacherresearch has been implemented in teacher education programs as a powerful,exploratory tool for teacher candidates to inquire about educational problemsand to improve their knowledge of teaching practice. This article presentsinsights gained from review of 18 action research projects completed byclassroom teachers enrolled in a graduate reading methods course. To betterunderstand what teachers learned through the action research process and howtheir self-study impacted teaching and learning in their classrooms,qualitative research methods were used to analyze the teachers' projects. Thedata revealed action research impacted literacy instruction, teachers struggledwith how to make their literacy instruction explicit, projects focused onspecific literacy topics, teachers used a range of resources for their selectedintervention and shared information with each other and with colleagues intheir respective contexts.